Houses of Mendicant Orders in the Venetian Messenia: the documentary evidence until 1500 (Case di ordini mendicanti nella Messenia veneziana: testimonianze documentarie fino al 1500) - Andrea Nanetti (2016)
The paper presents the documentary evidence to identify and locate the houses of the Mendicant Orders in Venetian Messenia (nowadays the Municipality of Pylos-Nestoras in Southern Peloponnese, Greece) between 13th and 15th centuries.